Prevalence of Mental Disorder among young adults in Ireland: a population based study. (26th February 2015) - Harley, M. E.; Connor, D.; Clarke, M. C.; Kelleher, I.; Coughlan, H.; Lynch, F.; Fitzpatrick, C.; Cannon, M.
Abstract : Background: There is a lack of epidemiological research on the mental health of young adults in Ireland. Objectives: To determine prevalence of psychiatric disorders in a cohort of young Irish adults. Methods: The Challenging Times study was a landmark study of the prevalence of psychiatric disorders in adolescents in North Dublin, Ireland: 212 school children aged 12-15 years were recruited through schools and interviewed using the K-SADS semi-structured diagnostic instrument. This cohort was traced again at age 19-24 years (mean age 20.8 years) and interviewed using SCID I & II. Main outcome measures were current and lifetime Axis I and Axis II psychiatric disorders. Results: Follow-up rate was 80%. Using a weighted population prevalence analysis 19.8% of the cohort had a current mental disorder, 56.0% had a lifetime mental disorder of whom 28.4% had mood disorders, 27.1% had anxiety disorders, 22.7% had substance use disorders; 25.4% had lifetime multi-morbidity. Cluster A personality disorders were found in 2.3%. Lifetime prevalence of binge-drinking was 75.0%, cannabis use 65% and 17% of young adults had fulfilled criteria for an alcohol use disorder at sometime in their life. Lifetime prevalence of suicidal thoughts/behaviour was 21.1%. Conclusions: Lifetime prevalence of psychiatric disorder and substance use were high in this sample of young Irish adults. Mental Health service provision for this age group is a priority. Larger studies of nationally representative samples are needed to inform service development.